Changes in blood insulin resistance, GLUT4 & AMPK after continuous and interval aerobic training in normal and diabetic rats - Mohammad Esmaiel Afzalpoura, Mohammad Reza Yousefib, Seyed Hossein Abtahi Eivaric, Saeed Ilbeigid (Journal of Applied Pharmaceutical Science, 2016)
Objectives: Diabetes mellitus is now seen as a worldwide epidemic disease with prevalent and incidence data. Exercise training is known to promote beneficial changes in diabetic patient.Materials & Methods: A number of 60 male rats weighing 180 to 310 grams, 13 weeks old were divided into six groups. The exercise protocol was aerobic training for six weeks. In this study, factors like Insulin resistance, glucose transporter type 4 and AMP-activated protein kinase were measured. The data were analyzed using one-way analysis of variance test in P< 0.05 level. Results: The results showed a significant difference in insulin resistance (P=0.001, F5, 37= 10.80), Glucose transporter type 4 (P=0.001, F5, 37= 20.14) and AMP-activated protein kinase (F5, 37 = 16.2, P= 0.001) levels among different groups. There was no significant difference between the impact of continuous and interval training on these indices (P=1.00).Conclusions: The continuous and interval training by increasing the Glucose transporter type4 protein content and AMP-activated protein kinase lead to reduced blood glucose levels and improved insulin resistance. Furthermore, we could use conducting interval training as a therapeutic approach to manage diabetes for the participants who were not able to perform the continuous training due to fatigue.
Keywords: Glucose transportertype4, Insulin resistance, Aerobic training, AMP-activated protein kinase.